(3OQGSGJ GdLOhi GdGbJUGOjI h GdeGdjIs - (3eMehO MSjf(B, (3GdhGOjs; (3SeMGf MSjf eMeO(B, s ((3YeGf(B:s (3OGQ UaGA ddfTQ hGdJhRjY(B,s, 2010)
(3JYQja GdGSJKeGQ h CfhGYg h CgOGag h eHGOF GJNGP GdbQGQ GdGSJKeGQj h eMOOGJ GdGSJKeGQ h CfhGY GdeTQhYGJ GdGSJKeGQjI h Cge GdeDSSGJ GdOhdjI aj eLGd Jehjd GdeTQhYGJ , eaghe OQGSI GdLOhi GdGbJUGOjI h GdeGdjI h CSGdjH GdeaGVdI Hjf GdHOGFd GdGSJKeGQjI h eYGjjQ Jbjje GdeTQhYGJ , OQGSI LOhiGdeTQhYGJ ef hLgI fXQ GSdGejIs
Keywords: (3GdEbJUGO GdeGdjs; (3GdGSJKeGQs; (3OQGSI GdLOhis